A case of isolated diffuse splenic haemangiomatosis in a dog. Issue 1 (24th March 2015) - Murgia, Daniela; Mori, Moira; Rondena, Marco; Tacchini, Damiana
Abstract : This report describes a case of isolated diffuse haemangiomatosis in the spleen of a nine‐month‐old dog that presented with weakness, abdominal discomfort and severe splenomegaly. Histopathological examination following splenectomy showed the splenic parenchyma had almost been replaced by multiple dilated vascular lacunae, varying is size, and lined by a single layer of flattened, well differentiated, endothelial cells sustained by fine fibrocystic bundles. The cytoplasmic expression of CD34 and von Willebrand factor found in the endothelial cells confirmed the vascular nature of the lesion; the lack of expression of podoplanin, a specific marker for the lymphatic vessels, excluded the diagnosis of lymphangiomatosis. Diffuse splenic haemangiomatosis carries a benign prognosis and complete cure following splenectomy has been described in humans and was achieved in this case. However, the differential diagnosis must take into account the possibility of vascular malignant or tumour‐like lesions occurring in the spleen.